Potential Short-Term Effects of Mine Tailings on Phytoplankton Assemblages in the Open Ocean - Dong Han Choi; Jangyeon Yoo; Wonseok Yang; Jae Hoon Noh; Yeonjung Lee; Kongtae Ra; Kiseong Hyeong; Chan Min Yoo; Jisoo Park (Journal of Marine Science and Engineering, 2022)
The disposal of mine tailings into the marine environment is considered an essential option to secure the economic efficiency of deep-sea mining, but it might adversely affects the ecosystem. To examine the potential impacts of tailing disposal from polymetallic nodules and polymetallic sulfide mines on phytoplankton communities, addition experiments of crushed fine particles into surface seawater were conducted in the open Indian Ocean and changes in chlorophyll a fluorescence and community composition were analyzed. The addition of tailings had serious adverse effects on phytoplankton fluorescence and photosynthetic activity, regardless of mine type. The adverse effects seemed to mainly be due to the physical properties of the mine tailings. These also showed discriminatory effects on phytoplankton, resulting in great changes in community composition. The results suggest that mine tailings could have significant adverse impacts on phytoplankton assemblages, but the degree of impact greatly varies depending on the phytoplankton groups. The discriminatory impacts would cause changes in biomass, community structure, and thus ecological function.